What's in a mass? - Calvete Chornet, Juan José (2021)
This short essay pretends to make the reader reflect on the concept of biological mass and on the added value that the determination of this molecular property of a protein brings to the interpretation of evolutionary and translational snake venomics research. Starting from the premise that the amino acid sequence is the most distinctive primary molecular characteristics of any protein, the thesis underlying the first part of this essay is that the isotopic distribution of a protein's molecular mass serves to unambiguously differentiate it from any other of an organism's proteome. In the second part of the essay, we discuss examples of collaborative projects among our laboratories, where mass profiling of snake venom PLA2 across conspecific populations played a key role revealing dispersal routes that determined the current phylogeographic pattern of the species.